Total Asam dan Sifat Organoleptik Yogurt Buah Cempedak (Artocarpus champaden L.): Total Acid and Organoleptic Properties of Cempedak Fruit Yogurt (Artocarpus champaden L.) - Puspita, Meilania Wisma; Wibawanti, Jeki Mediantari Wahyu; Mudawaroch, Roisu Eny (Jurnal Riset Agribisnis dan Peternakan, 2023)
This study aims to determine the total acid and organoleptic properties of yogurt added with cempedak fruit using the lactic acid bacteria Streptococcus thermophillus, Lactobacillus bulgaricus, and Lactobacillus acidhophillus. The treatment given was the addition of cempedak fruit pulp with concentrations of 0% (P0), 5% (P1), 10% (P2), and 15% (P3). The research used a completely randomized design (CRD) consisting of 4 treatments and 5 replications. The data obtained were analyzed using the Analysis of Variance (ANOVA) test, and if there were differences then the Duncan New Range Test (DMRT) was continued. Organoleptic tests were carried out using 50 slightly trained panelists. Organoleptic tests consist of hendonic quality and preferences (hedonics). Hedonic quality consists of the quality of color, taste, aroma, texture. The parameters of the research were total acid and organoleptics properties. The results showed that the addition of cempedak fruit had a significant effect (P<0.05) on total acid and organoleptic properties. The organoleptic test of the yogurt that the panelists liked most was yogurt with the addition of cempedak fruit pulp at the 15% level.